Royalti Karya Seni Musik Sebagai Harta Bersama dari Perspektif Hukum Kebendaan Perdata dan Kompilasi Hukum Islam - Frengki, Muhammad; Hakim, Arief Rachman (Legal Spirit, 2025)
This study aims to find out the legal perspective on civil law and the legal compilation of Islamic law in viewing the royalties on musical works as objects of joint property in marriage starting from the case in late 2023 of a musician sued by his wife in connection with the distribution of royalty on songs that have been created during marriage to be made equal to common property. This study uses methods of normative jurisprudential analysis with analysis of relevant legislative regulations and also previous research. The urgency of this research is that there is no law that clearly regulates that royalty can be used as joint property and ownership of its rights so that the laws in force at the moment can not respond and accommodate the needs of an increasingly dynamic society. Law as a non-final instrument will always be in a status of law in the making to adapt to the needs of society in its time. The results of this study indicate that the royalties on musical works still have the opportunity to be used as objects, in this case it is an object of joint property if referring to the theory of legal validity of Articles 499 of KUHPerdata and KHI especially Article 91(3) while keeping in mind the rights inherent in such musical works.